Development of E-Modules for Students’ Soft Skills in Facing the World of Work in English Subjects English Subject at SMKN 1 Batam - Wiswirya Deni; Fahmi Rizal; Ambiyar; Sukardi (Jurnal Penelitian Pendidikan IPA, 2025)
The purpose of this research is so that students to be able to learn independently by developing teaching materials for English learning e-modules in majoring mechatronics techniques that have suitable criteria, practical and effective. This study uses research and development (R&D) methods with a 4D (four-D) development model. This research stage includes define (defining stage), design (design stage), develop (development stage), and disseminate (dissemination stage). The instrument used in this study is a questionnaire that used to measure validity and practicality. Meanwhile, to measure the effectiveness of using a test instrument in the form of multiple choice questions. The research population was students of SMKN 1 Batam in majoring Industrial Automation techniques of XII class. The research results show that the e-module the subject of English was declared valid with a validity average value of 0.89 based on the validation of four material validators and in terms of media validity it was declared valid with a average value of 0.88 from three validators. E-modules are stated to be very practical based on teacher and student responses. This shows that, E-modules are effectively used as one of the teaching materials in learning to improving student learning outcomes.